2022
DOI: 10.1021/jacs.2c06718
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Development for Copper-Catalyzed Enantioconvergent Radical Cross-Coupling of Racemic Alkyl Halides

Abstract: The enantioconvergent cross-coupling of racemic alkyl halides represents a powerful tool for the synthesis of enantioenriched molecules. In this regard, the first-row transition metal catalysis provides a suitable mechanism for stereoconvergence by converting racemic alkyl halides to prochiral radical intermediates owing to their good single-electron transfer ability. In contrast to the noble development of chiral nickel catalyst, copper-catalyzed enantioconvergent radical cross-coupling of alkyl halides is le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 96 publications
0
38
0
2
Order By: Relevance
“…A visible-light-promoted stereoselective C­(sp 3 )-H glycosylation of quinolinyl-8 glycinates with modified carbohydrates bearing a redox active ester has been moreover shown to be promoted by a combination of copper­(II) triflate and (S)-PHANEPhos . A perspective article on ligand development for photoinduced copper-catalyzed enantioconvergent cross-coupling involving racemic alkyl halides has been recently published . A novel development in cooperative catalysis involving photoactivatable copper complexes has been reported, expanding the scope of biphotonic dual photoredox catalysts, by designing a system combining [Cu­(dap) 2 ]Cl (Cu­( NN 33 ) 2 ]­Cl) and 9,10-dicyanoanthracene under irradiation at 623 nm .…”
mentioning
confidence: 99%
“…A visible-light-promoted stereoselective C­(sp 3 )-H glycosylation of quinolinyl-8 glycinates with modified carbohydrates bearing a redox active ester has been moreover shown to be promoted by a combination of copper­(II) triflate and (S)-PHANEPhos . A perspective article on ligand development for photoinduced copper-catalyzed enantioconvergent cross-coupling involving racemic alkyl halides has been recently published . A novel development in cooperative catalysis involving photoactivatable copper complexes has been reported, expanding the scope of biphotonic dual photoredox catalysts, by designing a system combining [Cu­(dap) 2 ]Cl (Cu­( NN 33 ) 2 ]­Cl) and 9,10-dicyanoanthracene under irradiation at 623 nm .…”
mentioning
confidence: 99%
“…have accomplished a nickel‐catalyzed enantioconvergent radical C(sp 3 )−C(sp 3 ) cross‐coupling of tertiary α‐bromo‐β‐lactams with alkenes (Scheme 1B) [9a] . We have been focusing on developing the multidentate chiral ligand‐copper catalyst for realizing enantioconvergent radical cross‐coupling via a transmetalation/single‐electron reduction/bond formation sequence [7d, 11] . Very recently, we described an enantioconvergent C(sp 3 )−C(sp) cross‐coupling of the similar tertiary α‐bromo‐β‐lactams with alkynes utilizing the same mechanistic sequence (Scheme 1C) [12] .…”
Section: Methodsmentioning
confidence: 99%
“…As part of our ongoing endeavors in the enantioconvergent transformations, [7d, 11, 12] we herein report an enantioconvergent radical C(sp 3 )−C(sp 2 ) cross‐coupling of tertiary α‐bromo‐β‐lactams with aryl‐ and alkenylboronate esters. The key to the success is the utilization of a hemilabile N,N,N‐ligand to enhance the reducing capability of L* Cu(I) so that it could convert the highly reactive α‐bromo‐β‐lactam to a tertiary alkyl radical III via a single‐electron reduction process (Scheme 1D) [13] .…”
Section: Methodsmentioning
confidence: 99%
“…Recent research revealed that the metal-catalyzed radical relay strategy exhibited great translational potential for radical transformations, especially asymmetric radical synthesis . In this field, Liu, Feng, and Bao et.…”
mentioning
confidence: 99%